Surgical Approach In Vitreous Hemorrhage - Mirza Metita; Iwan Sovani; Arief Kartasasmita; Erwin Iskandar; Rova Virgana (International Journal of Retina, 2018)
Introduction: To report cases of retinal disorders that cause vitreous hemorrhage and the timing of pars plana vitrectomy in Cicendo Eye Hospital Methods: Retrospective observational study of all patients diagnosed with the vitreous hemorrhage who had undergone pars plana vitrectomy in 2016. Data were collected from medical record. Result: The mean age of this study is 54.65 years old from 260 vitreous hemorrhage patients. The most common retinal abnormalities are proliferative diabetic retinopathy (49.6%), wet age related macular degeneration (AMD) (13.5%), undetected retinal abnormalities (12.7%), retinal vein occlusion (8.8%), rhegmatogen retinal detachment (6.5%), trauma (3.45%), vasculitis (3.1%), idiopathic polypoidal choroidal vasculopathy (3.1%), and drop IOL (1.2%). PPV performed 1-3 months after initial assessment (31.25%), less than 1 month (13.2%), more than 3 months (14.6%) Conclusion: The most common etiology of vitreous hemorrhage is proliferative diabetic retinopathy. Pars plana vitrectomy was performed 1 – 3 months after an initial assessment of the patients.